From the factory to housing protecting working class memory in the “Fábrica Central de Leche”, Santiago de Chile - Ibarra, Macarena; Pontificia Universidad Católica de Chile. (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
This article concentrates in “Fábrica and Población Central de Leche”, in Santiago de Chile, as spaces were industrialheritage displays its tangible and intangible dimension and considering the working class memory related to bothits life in the factory and its domestic life. This case study is approached by considering the challenges of industrialheritage in Chile that goes from the state of researches around this topic, its own conceptual framework and the lackof normative agreements for its protection.The case of “Fábrica and Población Central de Leche” brings about three main clues that must be considered forstrenghing the protection of industrial heritage, in its intangible dimension: scale, temporality and methodology. Inthis way, the article proposes to approach industrial heritage from an urban scale, further to the industrial premises;in a wider temporal dimension were memory plays a central role in order to recover the history related to those spaces;and with a methodology were different disciplines interplay in order to study and examine the value of this heritage.